Multivariate analysis of walker-assisted ambulation - Martins, Maria M. (2013)
In an aging society it is extremely important to develop devices which can support and aid the elderly in their daily life. Walkers play an important role, due to the large number of potential users, its simplicity and their ambulatory potential. However, there are no clinical evidences that prove the efficacy of such devices, mainly rollators that present forearm supports. In this context, the authors aim to propose a protocol for an innovative gait analysis that addresses some benefits and limitations of these devices on the rehabilitation process, by addressing a multivariate analysis of spatiotemporal and kinematic gait parameters assessed during normal and assisted ambulation with a walker with forearm supports. For the 3Dreconstruction of the body segments it was used a movement analysis system. Results showed that the effects of assisted gait can be explained through support, energy consumption, posture and balance characteristics. These results are very satisfactory since aspects regarding these characteristics enhance the rehabilitation potential of the use of walkers with forearm supports. These results will be used to advance towards an active robotic walker that will provide for safety and natural manoeuvrability and offer a certain degree of intelligence in assistance and decision-making.